2001
DOI: 10.1097/00002826-200107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Increases the Motor Effects of L-Dopa in Parkinson's Disease: A Pilot Study

Abstract: We determined whether methylphenidate, a dopamine transporter blocker, modifies motor, cognitive, or affective responses to L-Dopa in Parkinson's disease (PD). Five patients who reported benefit from L-Dopa/carbidopa and motor fluctuations were admitted and withdrawn from their usual antiparkinsonian medications. On 3 consecutive days in a randomized double-blinded fashion, they took 0.2 mg/kg oral methylphenidate or placebo followed 30 minutes later by a 1-hour intravenous L-Dopa (2 mg/kg per h) or placebo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Results of a pilot study (n = 5) to determine the effects of methylphenidate as an adjunct to L -DOPA in Parkinson's disease (PD) demonstrated an increase in the motor effects of L -DOPA with the addition of methylphenidate. There were minimal effects on cognition and affect (with the exception of reaction time) [106] . Chronic administration of nicotine via transdermal patch has been found to have positive effects on cognition in AD and MCI, particularly in the subset of attention [107] .…”
Section: Discussionmentioning
confidence: 91%
“…Results of a pilot study (n = 5) to determine the effects of methylphenidate as an adjunct to L -DOPA in Parkinson's disease (PD) demonstrated an increase in the motor effects of L -DOPA with the addition of methylphenidate. There were minimal effects on cognition and affect (with the exception of reaction time) [106] . Chronic administration of nicotine via transdermal patch has been found to have positive effects on cognition in AD and MCI, particularly in the subset of attention [107] .…”
Section: Discussionmentioning
confidence: 91%
“…Because dopamine reuptake plays an important role in the regulation of dopamine in the synapse and the hypodopaminergic state is at the basis of much of the Parkinsonian syndrome, it has been suggested that MPH can improve motor function in PD. [135][136][137] Given the decline in attention abilities in PD and the putative reliance of a steady gait on this cognitive domain ͑recall the profound dual tasking effects͒, we hypothesized that MPH may also improve gait and reduce fall risk in patients with PD. 65 Twenty-one patients with PD were studied before and 2 h after administration of a single dose of 20 mg MPH.…”
Section: F Effects Of Methylphenidatementioning
confidence: 99%
“…These findings confirmed the results of our pilot study. 31 However, a study of another DAT inhibitor, branofensine, failed to find any effect of DAT inhibition on the response to an oral dose of L-dopa in eight PD subjects. 32 Differences in subjects and methods may explain the different results.…”
Section: Effects Of Methylphenidate On Antiparkinsonian Actions Of Brmentioning
confidence: 99%